An interactive Malaysian history mobile application for upper secondary school students in Malaysia / Nurul Hani Hassan - Hassan, Nurul Hani (2019)
Malaysian History subject is a compulsory subject that need to be learned by all students of Malaysia secondary school. However, the Malaysian History subject is not the most popular subject among the students. The students are required to understand and memorize the facts in order to answer all questions and score in the examination. Based on the conducted survey, most of the respondents (upper secondary school students) feel that the way of teaching and learning this subject need to be changed. The students feel that learning with textbook is unappealing to them. Thus, an interactive application is proposed to overcome this problem. The main objective of this project is to develop interactive mobile application that helps students to learn Malaysian History subject in more enjoyable and interactive way. The application is built using Sketchware. Sketchware is an application that enables the project to develop Android mobile application directly on mobile devices. It uses the combination of JAVA and Sketch, a block language that enables the project to go beyond prebuilt widgets, allowing the application to be flexible and scalable. The application consists of three chapters for Form 4 and Form 5 respectively. Thus, the chapters can be added in the future. Based on the survey conducted on thirty-one students, sixty-one percent of the students strongly agree that this application is easy to use and interactive since it combines audio, videos and pictures to attract the students into the world of Malaysian History. As the result, students can visualize, understand and appreciate the Malaysian History subject and also their own national history.